Windfall gains and stock market participation - Joseph Briggs; David Cesarini; Erik Lindqvist; Robert Östling (Research Institute of Industrial Economics (IFN), 2015)
We estimate the causal effect of wealth on stock market participation using administrative data on Swedish lottery players. A 150,000 windfall gain increases stock ownership probability among pre-lottery non-participants by 12 percentage points, while pre-lottery stock holders are unaffected. The effect is immediate, seemingly permanent and heterogeneous in intuitive ways. Standard lifecycle models predict wealth effects far too large to match our causal estimates under common calibrations. Additional analyses suggest a limited role for explanations such as procrastination or real-estate investment. Overall, results suggest that "nonstandard" beliefs or preferences contribute to the nonparticipation of households across many demographic groups.
Keywords: D1; G02; G11; 330; Stock market participation; Portfolio choice; Household finance